2014
DOI: 10.1111/pace.12386
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Venous Puncture in Electrophysiological Procedures: A Safe Method, Rapidly Learned

Abstract: UGVP is a short learning curve technique, significantly associated with a low incidence of minor VCs. This study supports wide use of UGVP in patients undergoing EP procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…This finding is a testament to the protective effect of US, apparent even in the cohort at greater risk for bleeding. Similar improved outcomes have been corroborated by publications from three other institutions, forming a robust experience that confirms the effectiveness of US in reducing vascular complications during EP procedures [13][14][15]. A summary of these four publications by Sobolev et al, including over 4000 subjects, showed a 60% reduction of major vascular complications and 66% reduction of minor ones [16].…”
supporting
confidence: 64%
“…This finding is a testament to the protective effect of US, apparent even in the cohort at greater risk for bleeding. Similar improved outcomes have been corroborated by publications from three other institutions, forming a robust experience that confirms the effectiveness of US in reducing vascular complications during EP procedures [13][14][15]. A summary of these four publications by Sobolev et al, including over 4000 subjects, showed a 60% reduction of major vascular complications and 66% reduction of minor ones [16].…”
supporting
confidence: 64%
“…Procedures were performed with vitamin K antagonist continuation with a target internalized normalized ratio of 2.0‐3.0, or direct oral anticoagulant (dabigatran, rivaroxaban, or apixaban given in the evening before the procedure if trans‐septal puncture was performed, or in the morning of the procedure in case of RA‐only ablation), under conscious sedation or general anesthesia in a fasting state. All catheters were advanced via the femoral vein after ultrasound‐guided venous puncture . A 6‐F steerable decapolar catheter (Irvine Bio Inc., St. Jude Medical Inc., St. Paul, MN, USA) was positioned in the CS, and served as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…Procedures were performed with vitamin K antagonist continuation with a target INR of 2.0–3.0. All catheters were advanced via the femoral vein under ultrasound guidance . Intravenous heparin was administered immediately after the insertion of the femoral sheaths, and continuously given to maintain an activated clotting time of 300–350 seconds throughout the procedure.…”
Section: Methodsmentioning
confidence: 99%